Draft Genome Sequencing of the Highly Halotolerant and Allopolyploid Yeast Zygosaccharomyces rouxii NBRC 1876 - Sato, Atsushi (Genome Announc, 2017)
The highly halotolerant and allopolyploid yeast Zygosaccharomyces rouxii is industrially used for the food production in high concentrations of salt, such as brewing soy sauce and miso paste. Here, we report the draft genome sequence of Z. rouxii NBRC 1876 isolated from miso paste.